Kinetics and vertical stiffness of female volleyball players: effect of low-intensity plyometric training - Rojano Ortega, D.; Berral-Aguilar, A. J.; Berral de la Rosa, F. J. (Research Quarterly for Exercise and Sport, 2022)
Purpose: The purpose of this study was threefold: 1) to assess kinematic/kinetic variables and vertical stiffness of recreational young female volleyball players during a vertical jump, 2) to identify the changes in those variables that occurred after low-intensity plyometric training, 3) to determine the relationship between stiffness and performance.